2020
DOI: 10.1021/acs.jpcc.9b11439
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Kinetics and Influence of Film Morphology on the Oxidation of Propene Thin Films by O(3P) Atomic Oxygen

Abstract: We present results detailing the oxidative reactivity of condensed propene thin films, with particular attention to epoxide product formation because of its importance in the industrial production of polyurethane plastics and the trace presence of these species in the interstellar medium. These studies were conducted in a state-of-the-art ultrahigh vacuum scattering instrument equipped for operation with cryogenic substrate temperatures. After exposing films to a supersonic beam of ground-state atomic oxygen, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 106 publications
(175 reference statements)
0
6
0
Order By: Relevance
“…Studies of O­( 3 P) reactions with acyclic unsaturated hydrocarbons show bimolecular pathways where products are formed on both the singlet PES and the triplet PES. Whereas the reaction of O­( 3 P) with acetylene (C 2 H 2 ) was found to occur exclusively on the triplet surface, in the reaction of O­( 3 P) with ethene (C 2 H 4 ), almost half of the products formed on the singlet PES after ISC, suggesting that in this simplest case, the rate of ISC competes with the rate of the reaction on the triplet surface.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of O­( 3 P) reactions with acyclic unsaturated hydrocarbons show bimolecular pathways where products are formed on both the singlet PES and the triplet PES. Whereas the reaction of O­( 3 P) with acetylene (C 2 H 2 ) was found to occur exclusively on the triplet surface, in the reaction of O­( 3 P) with ethene (C 2 H 4 ), almost half of the products formed on the singlet PES after ISC, suggesting that in this simplest case, the rate of ISC competes with the rate of the reaction on the triplet surface.…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1711 cm –1 peak is attributed to multilayer acetone or acetone–acetone interactions, this suggests that when the ASW film is thinner, fewer acetone molecules interact with water in the acetone–water interfacial region and that the water film is not yet self-similar; by self-similarity we mean that the structure of the interface is no longer varying with changes in thickness. Films less than 100 layers contain small islands that with increasing thickness converge to form a uniform film structure. ,, Thus, in contrast to the ultrathin films grown in previous studies, we chose to grow ice films of at least 150 layers to ensure that any differences observed with how acetone interacts with the CI, np-ASW, and p-ASW D 2 O ices are due to the underlying water coordination and not simply a film thickness effect.…”
Section: Resultsmentioning
confidence: 99%
“…The identification of glycerol and ethylene glycol in irradiated methanol ices exploiting PI-ReTOF-MS represents a particular success since both molecules have essentially indistinguishable infrared spectra, and classical FTIR cannot be utilized in their identification in complex mixtures . Fourth, our studies also revealed the mechanisms leading to the formation of the epoxides (cyclic ethers) ethylene oxide (c-C 2 H 4 O) and propylene oxide (c-C 3 H 6 O) via addition of suprathermal ground state oxygen (O­( 3 P)) or electronically excited oxygen (O­( 1 D)) to carbon–carbon double bonds of ethylene and propylene, respectively. Racemic propylene oxide represents the first chiral molecule detected in the interstellar medium .…”
Section: Resultsmentioning
confidence: 99%